A Beginner Can Be ‘Good Enough’: Seven Spiritual Disciplines of Pastoral Care and Spiritual Psychotherapy - Couture, Pamela D. 1951- (2022)
In order to replicate clinical supervision in the introductory classroom, the author breaks the learning task of pastoral care counseling into seven spiritual disciplines with a rationale for each. The integration of these practices over many years produces a seasoned practitioner.
Keywords: psychospiritual therapy; Spiritual Care; Pastoral Care; Pedagogy; clinical supervision; Spiritual Discipline